RELIGIUSITAS NASKAH DRAMA KAPAI-KAPAI KARYA ARIFIN C NOER (Dialog Tokoh, Kakek dan Koor) - Tuti Mutia (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2016)
The purpose of this study was to describe the values contained in theReligion plays Kapai-kapai Arifin C Noer work. The method used in this study isdeskriptif analysis method. The subject of this study, that the play wright RelgiusitasKapai-kapai Arifin C. Noer's work, and as the object of study is a play Kapai-kapai.Data collection techniques in this study using the method of determining the unit ofanalysis, data recording, and the process of inference and analysis.The results canbe the authors conclude that religiosity in a play Kapai-kapai Arifin C. Noer's workincludes: First, authentic religiosity or religiousness is directly coming from theheart. Includes prosecution toward better, please help and spiritual attitudes(conscience), seen very clearly in Abu dialogue and Grandfather. Both religiosityreligious or indirectly in response to God, man passes through a particular religionis formal and official. Clearly visible on the dialog Grandfather and Abu. The levelof religiosity Grandfather has more value than Abu. According Abu happy to begained when we merge with God. In essence, religiosity was looking nature of God.If you want to know God then had to go into it (religion), then just know God